Optimization of sonication process for high newcastle disease virus (NDV)titer - Nuhu Jaafar, Jaafar; Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Ideris, Aini; Syed Hassan, Sharifah (David Publishing, 2010)
Cell disruption focuses on obtaining a desired bioproduct within a cell, and it is the cell wall that must be disrupted to allow access to the contents of the cell. In animal cells, the plasma membrane is the only barrier separating cell contents from the environment.Sound waves from sonication, a mechanical technique for cell disintegration, have been used to disrupt as well as to aggregate cells as a step towards purification of a desired bioproduct. In the present study, an improved sonication process for the high yield of Newcastle disease virus (NDV) propagated in tissue culture was described. DF-1 cell was cultured in 25cm2 T flask. When cells were about 80 confluent, a lentogenic strain of NDV (F strain) was used to infect the cell monolayer. With evident cytopathic effect, cells were subjected to cycles of freeze-thaw before sonicating with varying combinations of amplitude, temperature and time. Cells were sonicated using a water bath Sonicator, Jac Ultrasonic 1505 JEIO TECH 4 KHz. From ANOVA analysis, a significant interaction between sonication time and amplitude was observed. This also corresponds to the highest F value observed.